PENGARUH IMPLEMENTASI SYARIAH GOVERNANCE TERHADAP LOYALITAS MUZAKKI (Studi Empiris pada Lembaga Amil Zakat di Yogyakarta) - Saffanatus Choiriyyah (AKT 16 UMY 111, 2016)
This study is conducted to examine and to find out the empirical evidence about the effect of implementation Syariah Governance toward loyalty of muzakki. The object of this research is the Institute Amil Zakat in Yogyakarta and the subjects in this study were muzaki been channeling their zakat Amil Zakat Institution. The method of this study is purposive sampling. The analysis tool is using double regression with SPSS 22 program. The result of this study showed that the independence variables are giving significant positive effect to the implementation of syariah governance that is tranparency and syariah compliance. But then, fairness, accountability, responsibility, and independence are not showing significant positive effect to the syariah governance Keywords : Fairness, Accountability, Responsibility, Independence, Syariah Compliance, Syariah Governance, Loyalty of Muzakki